Chemical Composition of the Essential Oil of Clausena heptaphylla W&A from Assam, India¶ - AHMAD, ATEEQUE; TANDON, SUDEEP; AHMAD, JAMIL; YADAV, ANJU (Asian Journal of Chemistry, 2010)
The essential oil obtained by hydrodistillation from the leaves of Clausena heptaphylla (W&A) from Assam, India was analyzed by GC and GC-MS. 16 Compounds representing 97.8 % of the total oil were identified of which (E)-anethole (92.6 %), (Z)-anethole (1.2 %) and methyl chavicol (1.6 %) were the major components. Eight minor components were unreported so far.